Preparation method of immobilized cellulase magnetic biochar and application of immobilized cellulase magnetic biochar in tobacco stem compost fermentation
By immobilizing cellulase magnetic biochar, the problem of low cellulose degradation efficiency in cow manure compost fermentation is solved, and higher thermal stability and cellulose degradation rate are achieved, which promotes the compost fermentation process and plant growth.
Patent Information
- Application Number
- CN202411779475.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-12-05
AI Technical Summary
The prior art is not efficient in promoting cellulose degradation in cow dung compost fermentation, and has high cost of method, large equipment demand or poor applicability.
Using the method of immobilizing cellulase magnetic biochar, the immobilization process of preparing magnetic biochar materials and cellulase is used to promote cellulose degradation in compost fermentation.
It improves the thermal stability of cellulase, shortens the compost fermentation cycle, improves the cellulose degradation rate and organic matter content, and promotes plant growth.
Smart Images

Figure CN119592550A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fertilizer fermentation, and in particular to a method for preparing immobilized cellulase magnetic biochar and application of the biochar in tobacco stem composting fermentation. Background Art
[0002] After cow dung compost is fermented, its nutrients include crude protein, crude fat, nitrogen-free extract, crude fiber and minerals, etc. It can be used as an organic fertilizer or substrate, which has a certain positive effect on improving soil quality and promoting plant growth. With the increasing awareness of organic food and environmental protection, the demand for cow dung as a high-quality organic fertilizer continues to increase, especially in the fields of green food and organic vegetables, the market demand for cow dung compost is strong. The country's support policy for agriculture has also brought a good development environment for the cow dung composting industry, making it an important part of the sustainable development of agriculture. Therefore, composting is a sustainable solution for organic waste and promotes the development of a circular economy model.
[0003] There are 4 main stages in the composting process: the first stage is the mesophilic stage or initial stage, with a rapid increase in temperature in the range of 10-42°C, dominated by mesophilic bacteria, and lasting for 24 to 72 hours; the second stage is the thermophilic stage, with a characteristic temperature between 45-70°C, and the degradation efficiency of organic compounds is closely related to the metabolic activity of thermophilic microorganisms, which can last for several days to weeks; the third stage is the maturation stage, with a temperature drop between 65 and 50°C and maintained for 1-2 months, and thermophilic microorganisms are reactivated to decompose the most difficult components to degrade; the last stage is the curing stage, which can last for 1-4 months, with a temperature between 50 and 23°C, and the converted organic matter accumulates steadily in these stages. The thermophilic fermentation in the second and third stages is the key period of the composting process. The thermophilic bacteria are the dominant functional microorganisms, and their metabolic activity at high temperatures determines the degradation efficiency of organic matter and limits the composting fermentation cycle. The cellulose content in cow dung is approximately between 30% and 50%, and the microbial fiber degradation activity is the core of the cow dung composting fermentation process.
[0004] At present, the methods for promoting the degradation of straw cellulose include chemical methods (alkalization treatment, acidification treatment, alkali-acid composite treatment and oxidant treatment), physical methods (supercritical carbon dioxide fluid pretreatment, microwave pretreatment, high temperature pyrolysis) and biological methods (special bacteria or composite bacteria). Although chemical treatment has good effects, it is costly and easy to pollute the environment, making it difficult to promote; physical methods have certain equipment requirements, high one-time investment costs, and site restrictions; while biological methods have unstable degradation efficiency and poor applicability.
[0005] Therefore, providing a method for preparing immobilized cellulase magnetic biochar suitable for cow dung fermentation is a technical problem that those skilled in the art urgently need to solve. Summary of the invention
[0006] In view of this, the present invention provides a method for immobilizing cellulase based on magnetic biochar material, and uses the cellulase-immobilized magnetic biochar material for composting.
[0007] To achieve the above object, the present invention adopts the following technical solution:
[0008] A method for preparing immobilized cellulase magnetic biochar comprises the following steps:
[0009] (1) Preparation of magnetic biochar materials
[0010] (1.1) Carboxylated biochar: The tobacco stems were rinsed with clean water and heated to dry, then crushed through a 60-mesh sieve and pyrolyzed by furnace burning to obtain biochar. The biochar was modified with nitric acid to increase the carboxyl groups on its surface, then rinsed with deionized water until the pH value was neutral, and dried to obtain carboxylated biochar.
[0011] (1.2) Photocatalytically active biochar: ZnSO4·7H2O and carboxylated biochar were mixed in deionized water and stirred to disperse evenly; NaOH solution was added dropwise under continuous magnetic stirring until the pH reached 10; the obtained mixture was transferred to a stainless steel autoclave lined with Teflon, sealed and heated, and then cooled to room temperature. The obtained product was washed with ethanol and deionized water, respectively, filtered, and dried to obtain ZnO-modified biochar carbon material; this material can inhibit the recombination of photogenerated electron-hole pairs due to the formation of a P / N heterojunction between ZnO and biochar, and has a strong photocatalytic activity.
[0012] (2) Preparation of modified Fe3O4@SiO2-NC nanoparticles
[0013] (2.1) Under a nitrogen atmosphere, FeCl3·6H2O and FeCl2·4H2O were dissolved in deionized water and stirred evenly. Under vigorous stirring, sodium hydroxide solution was added dropwise to the solution, and then heated and mixed, and the pH value of the solution was adjusted to 10. The solution was heated and mixed again, and then the obtained nanoparticles were separated by a magnet, and the nanoparticles were washed with pure water and ethanol, and impurities in the nanoparticles were removed by ultrasound, and dried to obtain Fe3O4 nanoparticles;
[0014] (2.2) The synthesized Fe3O4 nanoparticles were dispersed in deionized water, filtered, and the solution was added to ethanol and ultrasonically treated at 400 rpm for 20 min; then, ethyl silicate was added to the solution, and the reaction mixture was vigorously stirred at room temperature for 6 h under nitrogen; finally, the product was collected using a magnet, washed with water and ethanol, respectively, and dried under vacuum to obtain Fe3O4@SiO2-NC;
[0015] (2.3) Fe3O4@SiO2-NC was dispersed in ethanol by ultrasonication, and then APTES was added and vigorously stirred for 2 h at room temperature; the mixture was sealed in an autoclave and heated, and the mixture temperature was lowered to room temperature, the product was separated by a magnet and washed with ethanol to obtain aminosilane-modified Fe3O4@SiO2-NC;
[0016] (2.4) 1 g of TCT was dissolved in 20 mL of THF, and then aminosilane-modified Fe3O4@SiO2-NC was added to the solution and stirred evenly at room temperature. The product was collected by a magnet and the modified Fe3O4@SiO2-NC was washed with deionized water;
[0017] (3) Preparation of new magnetic biochar
[0018] The ZnO-modified biochar carbon material is dispersed in deionized water and evenly dispersed by ultrasonic treatment. Then, EDC and NHS are added to the solution together and stirred evenly at room temperature. The modified Fe3O4@SiO2-NC particles are suspended in deionized water by ultrasonication and then added to the biochar solution. The mixture is stirred to react, and the product is collected by magnetic separation, washed with deionized water and ethanol respectively, and dried to obtain a new type of magnetic biochar.
[0019] (4) Immobilization of cellulase
[0020] The new magnetic biochar was added into water, then cellulase was added, and then added into 50 mL of acetate buffer, and cultured in an incubator shaker at room temperature. The magnetic biochar loaded with cellulase was separated by a magnet, and washed with acetate buffer solution to obtain immobilized cellulase magnetic biochar.
[0021] Furthermore, the pyrolysis temperature in step (1.1) is 500° C. and the pyrolysis time is 2 h;
[0022] The nitric acid modification is as follows: 2.5 g of biochar is impregnated with 100 mL of 1+1 HNO3 at 60°C for 12 h;
[0023] The drying temperature is 60°C.
[0024] Further, the mass ratio of ZnSO4·7H2O to carboxylated biochar in step (1.2) is 2:3;
[0025] The concentration of the NaOH solution is 0.5 mol / L
[0026] The sealing temperature is 180°C and the sealing time is 12h;
[0027] The drying temperature is 70° C. and the drying time is 12 h.
[0028] Furthermore, in the technical solution of the present invention, the stirring rate of the vigorous stirring is 750 rpm.
[0029] Further, in step (2.1), the molar ratio of FeCl3·6H2O to FeCl2·4H2O is 2:1;
[0030] The concentration of the sodium hydroxide solution is 4M, and the mass ratio of the volume of the sodium hydroxide solution to FeCl3·6H2O is 10mL:3.4g;
[0031] The heating mixing temperature is 70°C, and the secondary heating mixing temperature is 80°C.
[0032] Further, the ratio of the mass of the Fe3O4 nanoparticles to the volume of deionized water to the volume of ethanol in step (2.2) is 5 g:150 mL:1500 mL;
[0033] The ratio of the mass of the Fe3O4 nanoparticles to the volume of ethyl silicate is 5g:4mL.
[0034] Furthermore, the mass ratio of Fe3O4@SiO2-NC to ethanol in step (2.3) is 1 g:100 mL;
[0035] The amount of APTES is 10% of the mass of Fe3O4@SiO2-NC;
[0036] The heating temperature is 90° C. and the heating time is 12 h.
[0037] Further, the mass ratio of TCT to THF in step (2.4) is 1 g:20 mL;
[0038] The mass ratio of the TCT to the aminosilane-modified Fe3O4@SiO2-NC is 1:3.
[0039] Further, the volume ratio of the mass of the ZnO-modified biochar carbon material to deionized water in step (3) is 100 mg:80 mL;
[0040] The mass ratio of the ZnO-modified biochar carbon material to EDC, NHS and modified Fe3O4@SiO2-NC is 100:30:20:100;
[0041] The stirring reaction temperature is 80°C and the stirring reaction time is 24h;
[0042] The drying temperature is 60° C. and the drying time is 6 hours.
[0043] Furthermore, the mass ratio of the novel magnetic biochar to the volume of the cellulase in step (4) is 60 mg:8 mL;
[0044] The concentration of the cellulase is 0.25 mg / mL;
[0045] The pH value of the acetate buffer is 5.
[0046] The present invention also provides the use of the immobilized cellulase magnetic biochar prepared by the above method in tobacco stem composting fermentation, comprising the following steps:
[0047] Tobacco stalks, cow dung, urea, corn flour and fermentation aids were mixed as a tobacco stalk compost matrix, immobilized cellulase was added and mixed evenly, water was added, and fermentation was carried out for 30 days;
[0048] The mass ratio of tobacco stems, cow dung, urea, corn flour, fermentation aids, immobilized cellulase magnetic biochar and water is 1000:300:5:5:4:5:60:250.
[0049] Furthermore, the fermentation aid is a base from Beijing Huaxia Kangyuan Technology Co., Ltd. 11 Leavening agent.
[0050] The beneficial effects of the present invention are as follows: the thermal stability of the cellulase prepared by the present invention after being fixed on the magnetic biochar material is improved, the cellulase activity is increased by 12% at 50°C, and the cellulase activity is increased by 50% after 60°C; the application of the cellulase-immobilized magnetic biochar material in the tobacco stalk and cow dung composting fermentation process can shorten the cycle by 30%, increase the cellulose degradation rate by 23.35%, and at the same time increase the organic matter content by 14.55%, the humic acid content by 6.38%, and the tobacco seedling germination rate by 23.35%.
[0051] The method of the invention can enhance the thermal stability of cellulase, and improve the enzyme activity of the cellulase by 10% to 170% under the same high temperature conditions (50 to 80° C.). This is because the magnetic biochar is a material with a porous structure. After being connected with the cellulase at multiple points, the firmness of the enzyme activity conformation is increased, while also inhibiting the degradation of the enzyme itself and partially blocking the invasion of external adverse factors on the enzyme, thereby improving the thermal stability of the enzyme. The invention utilizes the formation of a synthetic nano ZnO semiconductor material and a biochar P / N heterojunction to inhibit the recombination of photogenerated electron-hole pairs, improve the photocatalytic activity of the composite material, accelerate the degradation of cellulose under sunlight irradiation, and increase the organic matter content of the fermentation matrix. The low-concentration nano ZnO of the invention has a growth-promoting effect on plant growth, can improve the fresh quality of the aboveground part and the fresh quality of the root of the seedling, and can therefore be used as a source of zinc fertilizer for crop production. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] Figure 1 This is a diagram of the growth of tobacco seedling roots in tobacco stalk and cow dung compost substrate in Experimental Example 2 provided by the present invention. DETAILED DESCRIPTION
[0053] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0054] Example 1
[0055] A method for preparing immobilized cellulase magnetic biochar:
[0056] (1) Preparation of magnetic biochar materials
[0057] (1.1) Carboxylated biochar: The tobacco stems were rinsed with clean water and dried by heating, then crushed through a 60-mesh sieve and pyrolyzed at 500 °C for 2 h to obtain biochar. The biochar was modified with nitric acid by soaking 2.5 g of biochar in 100 mL (1+1) HNO3 at 60 °C for 12 h, then rinsed with deionized water until the pH was neutral, and dried at 60 °C for 10 h to obtain carboxylated biochar.
[0058] (1.2) Photocatalytically activated biochar: 2 g ZnSO4·7H2O and 3 g carboxylated biochar were mixed in 50 mL deionized water and stirred to disperse evenly; 0.5 mol / L NaOH solution was added dropwise under continuous magnetic stirring until the pH reached 10; the obtained mixture was transferred to a stainless steel autoclave lined with Teflon, sealed and kept at 180°C for 12 h, and then cooled to room temperature. The obtained product was washed with ethanol and deionized water, respectively, filtered, and then dried at 70°C for 12 h to obtain ZnO-modified biochar carbon material;
[0059] (2) Preparation of modified Fe3O4@SiO2-NC nanoparticles
[0060] (2.1) Under a nitrogen atmosphere, 3.4 g of FeCl3·6H2O and 1.25 g of FeCl2·4H2O (molar mass ratio 2:1) were dissolved in deionized water and stirred evenly. Under vigorous stirring at 750 rpm, 10 mL of sodium hydroxide solution (4 M) was added dropwise to the solution, and then mixed at a temperature of 70°C and the pH of the solution was adjusted to 10; the solution was mixed again at 80°C for 30 min, and then the obtained nanoparticles were separated by a magnet, washed with pure water and ethanol, and impurities in the nanoparticles were removed by ultrasound. Finally, the nanoparticles were dried at 70°C to obtain Fe3O4 nanoparticles;
[0061] (2.2) 5 g of the synthesized Fe3O4 nanoparticles were dispersed in 150 mL of deionized water, filtered, added to 1.5 L of ethanol, and ultrasonically treated at 400 rpm for 20 min; then, 4 mL of ethyl silicate was added to the solution, and the reaction mixture was vigorously stirred at room temperature and 750 rpm for 6 h under nitrogen; finally, the product was collected using a magnet, washed with water and ethanol, respectively, and dried under vacuum to obtain Fe3O4@SiO2-NC.
[0062] (2.3) 1 g of dried Fe3O4@SiO2-NC was dispersed in 100 mL of ethanol by ultrasonication, and then 10% APTES was added and stirred vigorously at 750 rpm for 2 h at room temperature; the mixture was sealed in an autoclave and heated at 90 °C for 12 h. The product was separated by a magnet by cooling the mixture temperature to room temperature and washed with ethanol to obtain aminosilane-modified Fe3O4@SiO2-NC;
[0063] (2.4) 1 g of TCT was dissolved in 20 mL of THF, and then 3 g of aminosilane-modified Fe3O4@SiO2-NC was added to the solution and stirred at room temperature for 2 h. The product was collected by a magnet and the modified Fe3O4@SiO2-NC was washed with deionized water;
[0064] (3) Preparation of new magnetic biochar
[0065] 100 mg ZnO-modified biochar carbon material was dispersed in 80 mL deionized water and ultrasonically treated for 30 min. Then 30 mg EDC and 20 mg NHS were added to the solution together and stirred at room temperature for 1 h. 100 mg modified Fe3O4@SiO2-NC particles were suspended in 20 mL deionized water by ultrasonication and then added to the biochar solution. The mixture was stirred and reacted at 80 °C for 24 h. The product was collected by magnetic separation, washed with deionized water and ethanol respectively, and then dried at 60 °C for 6 h to obtain a new type of magnetic biochar.
[0066] (4) Immobilization of cellulase
[0067] 60 mg of the new magnetic biochar was added to 2 mL of water, followed by 8 mL of cellulase (0.25 mg / mL), which was then added to 50 mL of acetate buffer at pH 5 and placed in an incubator oscillator at room temperature for 7 h. The magnetic biochar loaded with cellulase was separated with a magnet and washed with acetate buffer solution to obtain immobilized cellulase magnetic biochar.
[0068] Experimental Example 1 Determination of thermal stability of immobilized cellulase
[0069] Immobilized cellulase was prepared according to Example 1, and the activities of immobilized cellulase and non-immobilized cellulase were determined by carboxymethyl cellulose and dinitrosalicylic acid. The reaction conditions were 30°C, 40°C, 50°C, 60°C, 70°C, and 80°C for 1 h, respectively.
[0070] A carboxymethyl cellulose solution (1% (w / v)) prepared in 50 mM acetate buffer at pH = 5 was used as a substrate, and the color developer was dinitrosalicylic acid (1 gram of dinitrosalicylic acid dissolved in 50 milliliters of double distilled water). Then, 30 grams of potassium sodium tartrate and 20 milliliters of 2M sodium hydroxide solution were added. Distilled water was then added to make the final volume 100 mL, and the reagents were stored in a dark bottle. 1 mL of the enzyme solution from step 2 was added to a test tube containing 1 mL of carboxymethyl cellulose (1%) and placed at 50°C for 1 hour. 3 mL of dinitrosalicylic acid reagent was then added to the reaction mixture, and the sample and control were placed in boiling water for 15 minutes until a brown color appeared. The sample was then cooled and its absorbance was measured at 540 nm against the control using a glucose standard curve.
[0071] Table 1 Immobilized and free cellulase activities
[0072]
[0073]
[0074] As shown in Table 1, the activity of immobilized cellulase was higher than that of free cellulase at temperatures ranging from 40°C to 80°C. At 50°C, the activity of immobilized cellulase was 1.13 times that of free cellulase; at 70°C and 80°C, the activity of immobilized cellulase was 1.93 times and 2.73 times that of free cellulase, respectively. These results indicate that immobilized cellulase prepared based on modified magnetic biochar material has higher thermal stability.
[0075] Example 2
[0076] 1 kg of tobacco stems (crushed and sieved with 1 mm holes), 0.3 kg of cow dung, 0.005 kg of urea, 0.005 kg of corn flour, and 0.004 kg of fermentation aid were mixed as tobacco stem compost matrix, 0.06 kg of immobilized cellulase magnetic biochar prepared in Example 1 was added and mixed evenly, 250 mL of clean water was added, fermented for 30 days, and the cellulose content was detected.
[0077] Experimental Example 2 Application of immobilized cellulase in tobacco stem composting
[0078] According to Example 2, an application experiment of immobilized cellulase in tobacco stem and cow dung composting was carried out, and the experimental group was set up as follows.
[0079] Experimental group (T1): 1.314 kg compost matrix + 0.060 kg magnetic biochar material immobilized cellulase (scheme of Example 2);
[0080] Control group (T2): 1.314 kg compost substrate + 0.002 kg cellulase;
[0081] Control group (T3): 1.314 kg compost matrix + 0.060 kg modified magnetic biochar material;
[0082] Control group (T4): 1.314 kg compost matrix + 2 kg sodium alginate immobilized cellulase;
[0083] Control group CK: 1.314 kg compost substrate + 0.060 kg water.
[0084] Note: The amount of cellulase immobilized on magnetic biochar material and cellulase immobilized on sodium alginate is based on 0.002 kg of cellulase during preparation.
[0085] Sodium alginate immobilized cellulase is prepared by a conventional method. A mixed solution is prepared according to the ratio of sodium alginate: glutaraldehyde: cellulase: water = 3.5:1:0.1:100, and is dropwise injected into a 2% CaCl2 solution by mass. The gel beads are filtered out, placed in a replaced CaCl2 solution, and placed in a 4°C refrigerator to harden for 2 hours; the beads are filtered out again, washed three times with a 0.9% NaCl solution, and then rinsed twice with distilled water to obtain sodium alginate immobilized cellulase.
[0086] Table 2 Cellulose degradation rate after 30 days of tobacco stem and cow dung composting
[0087]
[0088] As shown in Table 2, the cellulose degradation rate of the experimental group (T1) with the addition of magnetic biochar immobilized cellulase was 22.74% ± 2.25%, which was higher than that of the control group with the addition of cellulase (T2), modified magnetic biochar material (T3) and sodium alginate immobilized cellulase (T4). Compared with the CK group, the cellulose degradation rate of the group with the addition of immobilized cellulase increased by an average of 30%, indicating that the cellulase immobilized magnetic biochar material can significantly promote cellulose degradation.
[0089] Table 3 Physical and chemical parameters after 30 days of tobacco stem and cow dung composting
[0090]
[0091]
[0092] As shown in Table 3, the cellulose organic matter content and humic acid content of the experimental group with the addition of magnetic biochar immobilized cellulase were significantly higher than those of T2, T3, T4 and CK, indicating that magnetic biochar immobilized cellulase can increase the organic matter and humic acid content of compost.
[0093] Table 4 Agronomic characteristics of tobacco seedlings grown with tobacco stem and cow dung compost
[0094]
[0095] The fermented compost of the experimental group and the control group was used as a substrate for tobacco seedling cultivation. After 14 days, the agronomic traits of the tobacco seedling root system were measured. The results are shown in Table 4 and Figure 1 As shown, the total root length of the experimental group T1 was 198.46 (±11.63) cm, and the total root surface area was 24.47 (±2.39) cm2. The two agronomic traits were significantly higher than those of the T2, T3, T4 and CK control groups, indicating that the magnetic biochar-immobilized cellulase-fermented tobacco stem and cow dung compost as a matrix can significantly promote the development of tobacco seedlings.
[0096] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A method for preparing immobilized cellulase magnetic biochar, characterized in that: The following steps are involved: (1) Preparation of magnetic biochar materials (1.1) Carboxylated biochar: The tobacco stems were rinsed with clean water and heated to dry, then crushed through a 60-mesh sieve, and then pyrolyzed by furnace burning to obtain biochar, which was modified with nitric acid, then rinsed with deionized water until the pH value was neutral, and dried to obtain carboxylated biochar; (1.2) Photocatalytically activated biochar: ZnSO4·7H2O and carboxylated biochar were mixed in deionized water and stirred to disperse evenly; NaOH solution was added dropwise under continuous magnetic stirring until the pH reached 10; the obtained mixture was transferred to a stainless steel autoclave lined with Teflon, sealed and heated, and then cooled to room temperature. The obtained product was washed with ethanol and deionized water, respectively, filtered, and dried to obtain ZnO-modified biochar carbon material; (2) Preparation of modified Fe3O4@SiO2-NC nanoparticles (2.1) Under a nitrogen atmosphere, FeCl3·6H2O and FeCl2·4H2O were dissolved in deionized water and stirred evenly. Under vigorous stirring, sodium hydroxide solution was added dropwise to the solution, and then heated and mixed, and the pH value of the solution was adjusted to 10. The solution was heated and mixed again, and then the obtained nanoparticles were separated by a magnet, and the nanoparticles were washed with pure water and ethanol, and impurities in the nanoparticles were removed by ultrasound, and dried to obtain Fe3O4 nanoparticles; (2.2) The synthesized Fe3O4 nanoparticles were dispersed in deionized water, filtered, and the solution was added to ethanol and ultrasonically treated at 400 rpm for 20 min; then, ethyl silicate was added to the solution, and the reaction mixture was vigorously stirred at room temperature for 6 h under nitrogen; finally, the product was collected using a magnet, washed with water and ethanol, respectively, and dried under vacuum to obtain Fe3O4@SiO2-NC; (2.3) Fe3O4@SiO2-NC was dispersed in ethanol by ultrasonication, and then APTES was added and vigorously stirred for 2 h at room temperature; the mixture was sealed in an autoclave and heated, and the mixture temperature was lowered to room temperature, the product was separated by a magnet and washed with ethanol to obtain aminosilane-modified Fe3O4@SiO2-NC; (2.4) 1 g of TCT was dissolved in 20 mL of THF, and then aminosilane-modified Fe3O4@SiO2-NC was added to the solution and stirred evenly at room temperature. The product was collected by a magnet and the modified Fe3O4@SiO2-NC was washed with deionized water; (3) Preparation of new magnetic biochar The ZnO-modified biochar carbon material was dispersed in deionized water and dispersed uniformly by ultrasonic treatment. Then, EDC and NHS were added to the solution together and stirred uniformly at room temperature. The modified Fe3O4@SiO2-NC particles were suspended in deionized water by ultrasonic treatment and then added to the biochar solution. The mixture was stirred for reaction. The product was collected by magnetic separation, washed with deionized water and ethanol respectively, and dried to obtain a new type of magnetic biochar. (4) Immobilization of cellulase The new magnetic biochar was added into water, then cellulase was added, and then added into 50 mL of acetate buffer, and cultured in an incubator shaker at room temperature. The magnetic biochar loaded with cellulase was separated by a magnet, and washed with acetate buffer solution to obtain immobilized cellulase magnetic biochar.
2. The method for preparing magnetic biochar with immobilized cellulase according to claim 1, characterized in that: The pyrolysis temperature in step (1.1) is 500°C and the pyrolysis time is 2h; The nitric acid modification is as follows: 2.5 g of biochar is impregnated with 100 mL of 1+1 HNO3 at 60°C for 12 h; The drying temperature is 60°C.
3. The method for preparing immobilized cellulase magnetic biochar according to claim 1, characterized in that: The mass ratio of ZnSO4·7H2O to carboxylated biochar in step (1.2) is 2:3; The concentration of the NaOH solution is 0.5 mol / L The sealing temperature is 180°C and the sealing time is 12h; The drying temperature is 70° C. and the drying time is 12 hours.
4. The method for preparing immobilized cellulase magnetic biochar according to claim 1, characterized in that: In step (2.1), the molar ratio of FeCl3·6H2O to FeCl2·4H2O is 2:1; The concentration of the sodium hydroxide solution is 4M, and the mass ratio of the volume of the sodium hydroxide solution to FeCl3·6H2O is 10mL:3.4g; The heating mixing temperature is 70°C, and the secondary heating mixing temperature is 80°C.
5. The method for preparing immobilized cellulase magnetic biochar according to claim 1, characterized in that: The ratio of the mass of the Fe3O4 nanoparticles to the volume of deionized water to the volume of ethanol in step (2.2) is 5 g:150 mL:1500 mL; The ratio of the mass of the Fe3O4 nanoparticles to the volume of ethyl silicate is 5g:4mL.
6. The method for preparing immobilized cellulase magnetic biochar according to claim 1, characterized in that: The mass ratio of Fe3O4@SiO2-NC to ethanol in step (2.3) is 1 g:100 mL; The amount of APTES is 10% of the mass of Fe3O4@SiO2-NC; The heating temperature is 90° C. and the heating time is 12 h.
7. The method for preparing immobilized cellulase magnetic biochar according to claim 1, characterized in that: The mass ratio of TCT to THF in step (2.4) is 1 g:20 mL; The mass ratio of the TCT to the aminosilane-modified Fe3O4@SiO2-NC is 1:
3.
8. The method for preparing magnetic biochar with immobilized cellulase according to claim 1, characterized in that: The volume ratio of the ZnO-modified biochar carbon material to deionized water in step (3) is 100 mg:80 mL; The mass ratio of the ZnO-modified biochar carbon material to EDC, NHS and modified Fe3O4@SiO2-NC is 100:30:20:100; The stirring reaction temperature is 80°C and the stirring reaction time is 24h; The drying temperature is 60° C. and the drying time is 6 hours.
9. The method for preparing magnetic biochar with immobilized cellulase according to claim 1, characterized in that: The mass ratio of the novel magnetic biochar to the volume of the cellulase in step (4) is 60 mg:8 mL; The concentration of the cellulase is 0.25 mg / mL; The pH value of the acetate buffer is 5.
10. Use of immobilized cellulase magnetic biochar prepared by the method according to any one of claims 1 to 9 in tobacco stem composting fermentation, characterized in that: The following steps are involved: Tobacco stalks, cow dung, urea, corn flour and fermentation aids were mixed as a tobacco stalk compost matrix, immobilized cellulase was added and mixed evenly, water was added, and fermentation was carried out for 30 days; The mass ratio of tobacco stems, cow dung, urea, corn flour, fermentation aids, immobilized cellulase magnetic biochar and water is 1000:300:5:5:4:5:60:250.
Citation Information
Patent Citations
Nano-grade ZnO loaded magnetic biological carbon composite photocatalyst and preparation method thereof
CN108311153A
Preparation method of immobilized laccase based on sodium hydroxide and ferroferric oxide crystal composite modified biochar
CN113930416A
Immobilized cellulase as well as preparation method and application thereof
CN119060999A
AU2020100293A4